Phosphorus-doped CoFe-LDH electrode for high-current hydrogen production as well as preparation method and application of phosphorus-doped CoFe-LDH electrode
The phosphorus-doped CoFe-LDH electrode was prepared by low-temperature hydrothermal method and template etching method, which solved the problem of insufficient activity of oxygen evolution electrodes in AEM water electrolytic cells, and achieved high-performance and long-life electrolytic hydrogen production effect, which was suitable for large-scale production.
Patent Information
- Application Number
- CN202511010901.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-09-02
AI Technical Summary
The oxygen evolution electrodes in existing AEM water electrolytic cells have insufficient activity and poor stability, resulting in large fluctuations in life and difficult to meet the expected performance standards.
The foamed nickel base material was doped by low-temperature hydrothermal method, and the phosphorus-doped CoFe-LDH electrode was prepared in combination with template etching method to form a porous array structure to improve the density of active sites and the stability of the catalyst.
It significantly improves the catalytic performance and stability of the electrode, can maintain efficient work for a long time under high current density, is low-cost and is suitable for large-scale production.
Smart Images

Figure CN120575231A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysis for hydrogen production by electrolysis of water, and particularly relates to the preparation of an electrode for high-current hydrogen production. Background Art
[0002] Hydrogen production by water electrolysis is one of the core technologies for achieving large-scale production of green hydrogen energy. As the latest water electrolysis technology, anion exchange membrane water electrolyzers have attracted the attention of many researchers and companies because they can use non-precious metal catalysts and have a wider range of membrane materials to choose from, which is expected to significantly reduce the cost of hydrogen production. However, in highly alkaline environments, the activity and stability of electrodes need to be urgently addressed. Due to the shortcomings of AEM electrodes in chemical and mechanical stability, their lifespan fluctuates greatly, making it difficult to achieve the expected performance standards. In-depth research has found that insufficient electrode conductivity, low active site density, and poor catalyst support interface stability are the key factors causing these problems.
[0003] In response to the problem of poor activity and stability of hydrogen production catalysts by water electrolysis, we have previously focused on the bimetallic layered hydroxide (LDH) catalyst system and conducted in-depth research. For example, patent application number 202110279084.7 discloses a multi-level structure nickel-cobalt bimetallic layered hydroxide material and its preparation method. The NiCo-LDH obtained using cobalt-based ZIFs as a template not only has a large surface area and high porosity, but also has controllable morphology and particle size, and has excellent electrochemical performance. However, NiCo-LDH also has limitations. Since the catalyst has no substrate support, it is made into a catalytic electrode by thermal spraying. During the thermal spraying process, high temperature easily leads to coarsening of the catalyst grains and reduces the density of active sites, which limits the large-scale application of the catalyst. Patent application number 202410011674.5 discloses a method for preparing a sulfur-substituted NiCo-LDH nanoarray material for high-current oxygen evolution. Using a sulfur-doping strategy, a three-dimensional sulfur-substituted NiCo-LDH nanoarray is in situ grown on carbon cloth. This material exhibits exceptional OER performance, particularly low overpotential at high current densities. However, the carbon cloth substrate serves only as a catalyst support and conductor during the catalytic process. Summary of the Invention
[0004] The present invention addresses the problems of insufficient activity and short stabilization time of oxygen evolution electrodes in AEM water electrolyzers, and provides a phosphorus-doped CoFe-LDH electrode for large-current hydrogen production, a preparation method, and an application. First, the phosphorus doping method is innovated, and the base material is phosphorus-doped by low-temperature hydrothermal treatment at 100-120°C, which not only reduces energy consumption but also enables large-scale production. Secondly, a phosphorus-doped CoFe-LDH electrode is developed by loading a catalyst on nickel foam through a template etching method. This method is significantly superior to traditional thermal spraying, electrodeposition, and other processes in terms of precise control of active sites, improved structural stability, and reduced process costs. It is particularly suitable for the preparation of high-performance, long-life water electrolysis electrodes. By developing efficient and low-cost catalysts, AEM alkaline water electrolysis technology is expected to become one of the feasible paths for large-scale hydrogen production. The electrode described in the present invention overcomes the defects of the existing technology, and has significantly improved catalytic performance, strong stability, and exhibits excellent electrocatalytic performance.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production comprises the following steps: 1) The nickel foam NF was soaked in a hydrochloric acid solution for pickling, then rinsed repeatedly with deionized water several times and stored in an ethanol solution for later use; 2) heating red phosphorus in an aqueous solution to uniformly disperse it to obtain a red phosphorus solution, immersing the NF obtained by acid washing in step 1) in the red phosphorus solution, placing it in a polytetrafluoroethylene-lined reactor for hydrothermal reaction, and repeatedly rinsing it with deionized water and drying it to obtain the product NiP; 3) Immersing the NiP obtained in step 2) in a mixed solution of cobalt acetate tetrahydrate and 2-methylimidazole, aging at room temperature, and after the reaction is completed, repeatedly rinsing with deionized water and drying to obtain the product Co-ZIF-L@NiP; 4) The Co-ZIF-L@NiP obtained in step 3) is immersed in a ferrous sulfate tetrahydrate solution and heated in a water bath for reaction. After repeated rinsing with deionized water and drying, a phosphorus-doped CoFe-LDH electrode CoFe-LDH@NiP for high-current hydrogen production is obtained.
[0006] Furthermore, in step 1), the concentration of hydrochloric acid is 0.1-3 mol / L, and the soaking time is 10-15 h. Preferably, the concentration of hydrochloric acid is 1 mol / L, and the soaking time is 12 h.
[0007] Furthermore, in step 2), the concentration of the red phosphorus solution is 0.01-1 mol / L, preferably 0.1 mol / L. The heating temperature is 50-70°C, preferably 60°C. The heating time is 1-3 hours, preferably 2 hours.
[0008] Furthermore, in step 2), the hydrothermal reaction temperature is 100-120°C for 4-10 hours. Low-temperature surface phosphating accelerates electron transfer between the substrate and the CoFe-LDH, significantly enhancing the intrinsic activity of the catalyst. Under hydrothermal conditions, phosphorus participates in the formation of an ultrathin, porous array of CoFe-LDH. This porous array structure increases the effective contact area between the electrolyte and the catalyst, significantly enhancing the exposure of active sites. The abundant mesoporous properties facilitate ion transport and the discharge of gaseous products.
[0009] Furthermore, in step 3), the molar ratio of cobalt acetate tetrahydrate to 2-methylimidazole is 1:(5-10), preferably 1:8.
[0010] Furthermore, in step 3), the aging time is 1-24 h, preferably 6 h.
[0011] Furthermore, in step 4), the concentration of the ferrous sulfate tetrahydrate solution is 2-5 mmol / L, preferably 3.6 mmol / L.
[0012] Furthermore, in step 4), the water bath temperature is 50-80° C., preferably 60° C. The water bath time is 2-30 min, preferably 15 min.
[0013] The drying in the above steps is performed by vacuum drying, the vacuum drying temperature is 60-80° C., preferably 60° C., and the drying time is 6-12 h, preferably 12 h.
[0014] The present invention also provides a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production prepared by the above method, in which phosphated nickel foam is selected as the base material, which not only has excellent conductivity, but also the phosphated nickel foam itself has many reactive active sites, which further enhances the electrochemical performance of the electrode. Low-temperature surface phosphating accelerates the electron transfer between the matrix and CoFe-LDH, significantly improving the intrinsic activity of the catalyst. At the same time, P participates in the construction of an ultra-thin porous array of CoFe-LDH under hydrothermal conditions. The porous array structure increases the effective contact area between the electrolyte and the catalyst, greatly increasing the exposure of the active sites, and the rich mesoporous properties are beneficial to the transport of ions and the discharge of gaseous products. The prepared CoFe-LDH@NiP composite electrode can reach 100 mA cm with an overpotential of only 225 mV in a 1 M KOH solution. -2 , the limiting current density can reach 500 mA cm -2 , and can operate stably for 80 h while still maintaining a current density of more than 90%.
[0015] The present invention also provides an application of a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production in an AEM water electrolyzer. The AEM water electrolyzer exhibits significant activity at a voltage of 1.85 V, reaching 100 mA cm -2 The current density is 100 mA cm -2 The performance of the RuO2 was significantly better than that of commercial RuO2 (24h) when it can operate stably for 70h at high current density without obvious performance degradation.
[0016] Compared with the prior art, the present invention has the following advantages: (1) This invention constructs a multi-layered CoFe-LDH@NiP composite electrode through low-temperature surface phosphating and template etching strategies. CoFe-LDH is arranged in an array on the NiP surface. The porous array structure greatly exposes the active sites and effectively increases the contact between the catalyst and the electrolyte. The multi-column array structure improves the catalytic performance of CoFe-LDH, and the rich mesoporous properties facilitate the timely removal of reaction products, further extending the service life of the electrode.
[0017] (2) Bimetallic electrocatalysts can effectively regulate the electronic structure and catalytic activity of materials by introducing a synergistic effect between two different metal elements. The core advantage of the phosphorus-doped CoFe-LDH described in the present invention lies in the synergistic regulation mechanism of the bimetallic (Co / Fe) and phosphorus atoms. Specifically, the doping of P causes the metallic bond between Co and Fe to change in length, triggering a lattice strain effect, thereby changing the electronic structure. This results in the excellent OER performance of the phosphorus-doped CoFe-LDH electrode.
[0018] (3) The phosphorus-doped CoFe-LDH electrode described in the present invention has the advantages of simple process, low cost, high efficiency and low energy consumption in the production process. The raw materials used are low in cost and meet green environmental protection standards. It can be mass-produced and shows good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0020] Figure 1 This is a scanning electron microscope image of Example 1 of the present invention; Figure 2(a) is a transmission electron micrograph of Example 1 of the present invention; (b) is a high-resolution transmission electron micrograph of Example 1 of the present invention; (c) is a Fourier-transformed atomic phase and SAED illustration of Example 1 of the present invention; (d) is an energy-dispersive X-ray spectroscopy elemental mapping diagram of Example 1 of the present invention; Figure 3 The linear sweep voltammetry curves of Examples 1, 2, and 3 of the present invention and Comparative Examples 1, 2, and 3 are shown; Figure 4 Tafel slope curves of Examples 1, 2, and 3 of the present invention and Comparative Examples 1, 2, and 3 during the OER process; Figure 5 The active specific surface area curves of Example 1 of the present invention and Comparative Examples 1, 2, and 3 are shown; Figure 6 Electrochemical impedance spectra of Example 1 of the present invention and Comparative Examples 1, 2, and 3; Figure 7 Example 1 of the present invention at 200 mA cm -2 Chronoamperometric test curve under current density; Figure 8 Current-voltage curves of an AEM electrolytic cell using Example 1 of the present invention and Comparative Example 1 and using commercial RuO2 coated on a titanium metal felt as an anode and commercial PtC coated on a titanium metal felt as a cathode in a 1 M KOH electrolyte; Figure 9 The AEM electrolytic cell of Example 1 of the present invention with commercial RuO2 coated on titanium metal felt as anode and commercial PtC coated on titanium metal felt as cathode was operated at 100 mA cm -2 Room temperature test curve for the run. DETAILED DESCRIPTION
[0021] The technical solutions of the present invention are further described in detail below in conjunction with specific embodiments. The description of the technical features described below is based on representative implementation schemes and specific examples of the present invention, but the present invention is not limited to these implementation schemes and specific examples.
[0022] In the following examples, the raw materials used are all common commercial products that can be purchased directly or can be prepared using conventional techniques in the art.
[0023] Room temperature refers to 25±°C.
[0024] Example 1 A method for preparing a phosphorus-doped CoFe-LDH electrode for high current density water electrolysis, the specific method comprising the following steps: (1) Pretreatment of NF substrate First, a piece of 2×3 cm 2The nickel foam was immersed in 1 mol / L hydrochloric acid solution for 12 h, then washed repeatedly with deionized water several times and stored in ethanol solution for later use.
[0025] (2) Preparation of NiP-120 0.1 g of red phosphorus was heated in 30 mL of deionized water at 60°C for 2 h. After the red phosphorus was evenly dispersed, it was placed in a 50 mL polytetrafluoroethylene-lined reactor together with the NF obtained in step (1) and hydrothermally reacted at 120°C for 6 h. After the reaction was completed, the reactor was cooled to room temperature naturally, the NF was removed and repeatedly washed with deionized water, and finally dried under vacuum for 12 h to obtain NiP-120.
[0026] (3) Preparation of Co-ZIF-L@NiP-120 Dissolve 2 mmol of cobalt acetate tetrahydrate and 16 mmol of 2-methylimidazole in 40 mL of deionized water. Mix the two rapidly with high-speed stirring. Immerse the NiP-120 obtained in step (2) in the mixed solution and age it at room temperature for 6 h. After the reaction is complete, rinse it repeatedly with deionized water and dry it in a vacuum drying oven at 60°C for 12 h to obtain Co-ZIF-L@NiP-120.
[0027] (4) Preparation of CoFe-LDH@NiP-120 50 mg of ferrous sulfate tetrahydrate was dissolved in 50 mL of deionized water. Co-ZIF-L@NiP-120 was immersed in the ferrous sulfate solution and heated to 60°C for 15 min. After the reaction, it was repeatedly rinsed with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain CoFe-LDH@NiP-120.
[0028] Figure 1 This is a scanning electron microscope image of Example 1 of the present invention. It can be seen that CoFe-LDH presents a regular array structure on NiP-120 and has rich mesoporous properties, which provides a guarantee for the exposure of active sites and the transmission of substances.
[0029] Figure 2 (a) is a transmission electron microscopy image of Example 1 of the present invention, showing that CoFe-LDH is composed of many tiny ultrathin nanosheets, which is consistent with the SEM results; Figure 2 (b) is a high-resolution transmission electron microscopy image of Example 1 of the present invention, from which clear lattice fringes can be seen, accompanied by partial amorphous regions, which increase the number of active sites; Figure 2 (c) is the atomic phase of Example 1 of the present invention after Fourier transformation and its SAED illustration. The atomic phase shows a larger lattice spacing of d (012)= 0.263 nm and d (003) =0.334 nm, which means a greater degree of lattice distortion, indicating that some P atoms are introduced into the lattice. SAED also shows obvious diffraction rings and no diffraction spots, corresponding to the (003), (006) and (012) crystal planes respectively; Figure 2 (d) is an energy dispersive X-ray spectroscopy element mapping diagram of Example 1 of the present invention. From the figure, the element distribution of Example 1 can be seen. Ni, Fe, Co, O and P elements all show obvious signals, indicating that Example 1 was successfully synthesized.
[0030] Example 2 Steps (1), (2), and (3) of Example 2 are as described in Example 1. The difference between Example 2 and Example 1 is that in step (4), the heating time is 2 minutes, and the specific method is as follows: (4) Preparation of CoFe-LDH@NiP-120 50 mg of ferrous sulfate tetrahydrate was dissolved in 50 mL of deionized water. Co-ZIF-L@NiP-120 was immersed in the ferrous sulfate solution and heated to 60°C for 2 min. After the reaction was completed, it was repeatedly rinsed with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain CoFe-LDH@NiP-120.
[0031] Example 3 Steps (1), (2), and (3) of Example 3 are as described in Example 1. The difference between Example 3 and Example 1 is that in step (4), the heating time is 30 min, and the specific method is as follows: (4) Preparation of CoFe-LDH@NiP-120 50 mg of ferrous sulfate tetrahydrate was dissolved in 50 mL of deionized water. Co-ZIF-L@NiP-120 was immersed in the ferrous sulfate solution and heated to 60°C for 30 min. After the reaction was completed, it was repeatedly rinsed with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain CoFe-LDH@NiP-120.
[0032] Example 4 This embodiment provides a method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production, comprising the following steps: 1) The nickel foam NF was soaked in a 0.1 mol / L hydrochloric acid solution for 10 h for acid washing, then rinsed several times with deionized water and stored in an ethanol solution for later use; 2) Red phosphorus was heated in a 50°C aqueous solution for 1 hour to obtain a 0.01 mol / L red phosphorus solution after uniform dispersion. The NFs, acid-washed in step 1), were immersed in the red phosphorus solution and placed in a polytetrafluoroethylene-lined reactor. The NFs were hydrothermally reacted at 100°C for 10 hours. The NFs were then rinsed repeatedly with deionized water and dried at 60°C for 12 hours to obtain the product NiP. 3) Immersing the NiP obtained in step 2) in a mixed solution of cobalt acetate tetrahydrate and 2-methylimidazole, wherein the molar ratio of cobalt acetate tetrahydrate to 2-methylimidazole is 1:5, and aging at room temperature for 1 hour. After the reaction is completed, the mixture is repeatedly rinsed with deionized water and dried at 60°C for 12 hours to obtain the product Co-ZIF-L@NiP; 4) The Co-ZIF-L@NiP obtained in step 3) was immersed in a 2 mmol / L ferrous sulfate tetrahydrate solution and heated in a 50°C water bath for 30 min. After repeated rinsing with deionized water and drying at 60°C for 12 h, a phosphorus-doped CoFe-LDH electrode CoFe-LDH@NiP for high current hydrogen production was obtained.
[0033] Example 5 This embodiment provides a method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production, comprising the following steps: 1) The nickel foam NF was soaked in a 3 mol / L hydrochloric acid solution for 10 h for acid washing, then rinsed several times with deionized water and stored in an ethanol solution for later use; 2) Red phosphorus was heated in an aqueous solution at 70°C for 1 hour to obtain a 1 mol / L red phosphorus solution after uniform dispersion. The NFs, acid-washed in step 1), were immersed in the red phosphorus solution and placed in a polytetrafluoroethylene-lined reactor. The reaction was hydrothermally reacted at 120°C for 4 hours. The product, NiP, was obtained after repeated rinsing with deionized water and drying at 80°C for 6 hours. 3) Immersing the NiP obtained in step 2) in a mixed solution of cobalt acetate tetrahydrate and 2-methylimidazole, wherein the molar ratio of cobalt acetate tetrahydrate to 2-methylimidazole is 1:10, and aging at room temperature for 24 hours. After the reaction is complete, the mixture is repeatedly rinsed with deionized water and dried at 80°C for 6 hours to obtain the product Co-ZIF-L@NiP; 4) The Co-ZIF-L@NiP obtained in step 3) was immersed in a 2-5 mmol / L ferrous sulfate tetrahydrate solution and heated in an 80°C water bath for 2 min. After repeated rinsing with deionized water and drying at 80°C for 6 h, a phosphorus-doped CoFe-LDH electrode CoFe-LDH@NiP for high-current hydrogen production was obtained.
[0034] Example 6 This embodiment provides a method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production, comprising the following steps: 1) The nickel foam NF was soaked in a 1 mol / L hydrochloric acid solution for 13 h for acid washing, then rinsed several times with deionized water and stored in an ethanol solution for later use; 2) Red phosphorus was heated in an aqueous solution at 60°C for 2 h to obtain a 0.05 mol / L red phosphorus solution after uniform dispersion. The NF obtained by acid washing in step 1) was immersed in the red phosphorus solution and placed in a polytetrafluoroethylene-lined reactor for hydrothermal reaction at 110°C for 8 h. The product NiP was obtained after repeated rinsing with deionized water and drying at 70°C for 10 h. 3) Immersing the NiP obtained in step 2) in a mixed solution of cobalt acetate tetrahydrate and 2-methylimidazole, wherein the molar ratio of cobalt acetate tetrahydrate to 2-methylimidazole is 1:8, and aging at room temperature for 12 hours. After the reaction is complete, the mixture is repeatedly rinsed with deionized water and dried at 70°C for 10 hours to obtain the product Co-ZIF-L@NiP; 4) The Co-ZIF-L@NiP obtained in step 3) was immersed in a 3 mmol / L ferrous sulfate tetrahydrate solution and heated in a 70°C water bath for 20 min. After repeated rinsing with deionized water and drying at 70°C for 10 h, a phosphorus-doped CoFe-LDH electrode CoFe-LDH@NiP for high current hydrogen production was obtained.
[0035] Comparative Example 1 Compared with Example 1 of the present invention, the difference of Comparative Example 1 is that the NF substrate is not phosphated, and the specific method is according to the following steps: (1) Pretreatment of NF substrate First, a piece of 2×3 cm 2 The nickel foam was immersed in 1 mol / L hydrochloric acid solution for 12 h, then washed repeatedly with deionized water several times and stored in ethanol solution for later use.
[0036] (2) Preparation of Co-ZIF-L@NF Dissolve 2 mmol of cobalt acetate tetrahydrate and 16 mmol of 2-methylimidazole in 40 mL of deionized water. Mix the two rapidly with high-speed stirring. Immerse the NF obtained in step (1) in the mixed solution and age it at room temperature for 6 h. After the reaction is complete, rinse it repeatedly with deionized water and dry it in a vacuum drying oven at 60°C for 12 h to obtain Co-ZIF-L@NF.
[0037] (3) Preparation of CoFe-LDH@NF 50 mg of ferrous sulfate tetrahydrate was dissolved in 30 mL of deionized water. The metal salt solution was placed in a water bath and heated to 60°C. The Co-ZIF-L@NF obtained in step (2) was then immersed in the solution for 15 min. After the reaction was completed, it was repeatedly rinsed with deionized water and dried in a vacuum drying oven at 60°C for 12 h to obtain CoFe-LDH@NF.
[0038] Comparative Example 2 Compared with Example 1 of the present invention, the difference between Comparative Example 2 is that CoFe-LDH is not loaded, and the specific method is according to the following steps: (1) Pretreatment of NF substrate First, a piece of 2×3 cm 2 The nickel foam was immersed in 1 mol / L hydrochloric acid solution for 12 h, then washed repeatedly with deionized water several times and stored in ethanol solution for later use.
[0039] (2) Preparation of NiP-120 0.1 g of red phosphorus was heated in 30 mL of deionized water at 60°C for 2 h. After the red phosphorus was evenly dispersed, it was placed in a 50 mL polytetrafluoroethylene-lined reactor together with the NF obtained in step (1) and hydrothermally reacted at 120°C for 6 h. After the reaction was completed, the reactor was cooled to room temperature naturally, the NF was removed and repeatedly washed with deionized water, and finally dried under vacuum for 12 h to obtain NiP-120.
[0040] Comparative Example 3 Compared with Example 1 of the present invention, the difference between Comparative Example 3 is that it is not phosphated and CoFe-LDH is not loaded. The specific method is according to the following steps: A piece of 2×3 cm 2 The nickel foam was immersed in 1 mol / L hydrochloric acid solution for 12 h, then washed repeatedly with deionized water several times and stored in ethanol solution for later use.
[0041] Electrochemical performance test The electrochemical properties were tested using a standard three-electrode system, with the electrodes described in Example 1 and Comparative Examples 1-3 of the present invention as working electrodes, a carbon rod as a counter electrode, and a mercury / mercuric oxide electrode as a reference electrode. The tests were performed in 1 M KOH solution.
[0042] Figure 3 The linear sweep voltammetry curves of Examples 1, 2, and 3 of the present invention and Comparative Examples 1, 2, and 3 show that Example 1 of the present invention has a lower overpotential, which reaches 50 mA cm -2 , 100 mA cm -2 and 300 mA cm -2The overpotentials are 225, 256, and 307 mV, respectively, demonstrating the superiority of the present catalyst.
[0043] Figure 4 The Tafel slope curves of Examples 1, 2, and 3 of the present invention and Comparative Examples 1, 2, and 3 during the OER process are shown in FIG. The Tafel slope is greater than that of Example 1 (62.20 mv dec -1 )<Comparative Example 1(89.98 mv dec -1 )<Example 2(120.92 mvdec -1 ) is smaller than Example 3 (147.32 mv dec -1 )<Comparative Example 2(212.63 mv dec -1 )<Comparative Example 3(270.71 mvdec -1 ), a lower Tafel slope means that the catalyst has a faster reaction kinetic process, which further illustrates that Example 1 of the present invention has better catalytic activity.
[0044] Figure 5 The active specific surface area diagram of Example 1 of the present invention and Comparative Examples 1, 2 and 3, wherein C dl The values are 26.95 mF cm -2 , 16.03 mF cm- 2 , 8.01 mF cm -2 and 3.44 mF cm -2 Since ECSA and C dl It shows a strict linear relationship, so Example 1 has the largest ECSA, which shows that the presence of the phosphide intermediate layer also plays a very important role in the surface morphology evolution of the catalyst. It also means that it can expose more active sites to participate in the catalytic process, which is a key factor in enhancing catalytic performance.
[0045] Figure 6 The electrochemical impedance spectra of Example 1 of the present invention and Comparative Examples 1, 2 and 3 show that Example 1 exhibits a smaller Nyquist semicircle in the low-frequency region, indicating extremely low charge transfer resistance and mass transfer rate, further proving the key role of the intermediate phosphide layer in improving OER performance.
[0046] Figure 7 This is the chronoamperometric test curve of Example 1 of the present invention. Example 1 is tested at 200 mA cm -2 The catalytic performance of Example 1 was excellent, and the electrolytic performance was stable at a high current density of 100 ℃ for 80 h, while maintaining a catalytic efficiency of more than 90%. This excellent durability indicates the potential of Example 1 for industrial water electrolysis.
[0047] Electrolyzed water performance test The electrolysis of water is carried out in an alkaline electrolytic cell made of titanium and equipped with a cathode / anode peristaltic pump to achieve bidirectional circulation of the electrolyte. The flow channel area is 1*1 cm 2 The anion exchange membrane used was FAA-3-75. In Example 1 of the present invention and Comparative Example 1, commercial RuO2 coated on titanium metal felt was used as the anode, and commercial PtC coated on titanium metal felt was used as the cathode.
[0048] Figure 8 The current-voltage curves of the AEM electrolytic cell using Example 1 of the present invention and Comparative Example 1 and commercial RuO2 coated on titanium metal felt as anode and commercial PtC coated on titanium metal felt as cathode in 1 M KOH electrolyte are shown. It can be seen that the AEM electrolytic cell using Example 1 as anode exhibits significant activity at a voltage of 1.85 V, reaching 100 mA cm -2 The current density is even better than that of commercial RuO2 (2.23 V).
[0049] Figure 9 The AEM electrolytic cell of Example 1 of the present invention with commercial RuO2 coated on titanium metal felt as anode and commercial PtC coated on titanium metal felt as cathode was operated at 100 mA cm -2 The room temperature test curve of the high current density operation is shown in Figure 1. The AEM electrolytic cell using Example 1 as the anode can -2 The electrolytic cell can stably operate at a current density of 1000 nm for 70 h without any obvious performance degradation, while the AEM electrolytic cell with commercial RuO2 coated on titanium metal felt as the cathode has obvious degradation. After 24 h of operation, its current density has decayed by 50%, which proves the superiority of Example 1 of the present invention in the AEM electrolytic cell.
[0050] In summary, the present invention has successfully developed a high-performance AEM water electrolysis electrode under the premise of precise control of active sites, improved structural stability, and reduced process costs. When the electrode is applied to the AEM water electrolysis device, it can achieve 100 mA cm at an operating voltage of 1.85 V. -2 The high current density is better than that of commercial RuO2. -2 At high current density, the electrode material exhibits excellent durability, operating stably for 70 hours without significant performance degradation. The electrodes prepared by this invention combine high activity with a long lifespan, providing reliable technical support for the realization of high-performance, low-cost water electrolysis hydrogen production systems and demonstrating significant industrial application value.
[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production, characterized in that: The following steps are involved: 1) The nickel foam NF was soaked in a hydrochloric acid solution for pickling, then rinsed repeatedly with deionized water several times and stored in an ethanol solution for later use; 2) heating red phosphorus in an aqueous solution to uniformly disperse it to obtain a red phosphorus solution, immersing the NF obtained by acid washing in step 1) in the red phosphorus solution, placing it in a polytetrafluoroethylene-lined reactor for hydrothermal reaction, and repeatedly rinsing it with deionized water and drying it to obtain the product NiP; 3) Immersing the NiP obtained in step 2) in a mixed solution of cobalt acetate tetrahydrate and 2-methylimidazole, aging at room temperature, and after the reaction is completed, repeatedly rinsing with deionized water and drying to obtain the product Co-ZIF-L@NiP; 4) The Co-ZIF-L@NiP obtained in step 3) is immersed in a ferrous sulfate tetrahydrate solution and heated in a water bath for reaction. After repeated rinsing with deionized water and drying, a phosphorus-doped CoFe-LDH electrode CoFe-LDH@NiP for high-current hydrogen production is obtained.
2. The method for preparing the phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 1), the concentration of hydrochloric acid is 0.1-3 mol / L, and the soaking time is 10-15 h.
3. The method for preparing the phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 2), the concentration of the red phosphorus solution is 0.01-1 mol / L, the heating temperature is 50-70°C, and the heating time is 1-3 h.
4. The method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 2), the hydrothermal reaction temperature is 100-120°C and the reaction time is 4-10 h.
5. The method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 3), the molar ratio of cobalt acetate tetrahydrate to 2-methylimidazole is 1:(5-10).
6. The method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 3), the aging time is 1-24 h.
7. The method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 4), the concentration of the ferrous sulfate tetrahydrate solution is 2-5 mmol / L.
8. The method for preparing a phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 1, characterized in that: In step 4), the water bath temperature is 50-80°C, and the water bath time is 2-30 min.
9. A phosphorus-doped CoFe-LDH electrode for high-current hydrogen production prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the phosphorus-doped CoFe-LDH electrode for high-current hydrogen production according to claim 9 in water electrolysis in an AEM electrolyzer, characterized in that: It showed remarkable activity at a voltage of 1.85 V, reaching 100 mA cm -2 The current density is 100 mA cm -2 The performance can be stably operated for 70 h at a high current density without any obvious performance degradation.
Citation Information
Patent Citations
A multi-level nickel-cobalt bimetallic layered hydroxide material and its preparation method
CN113096965B
Preparation method of sulfur atom substituted NiCo LDH nano array material for large-current oxygen evolution
CN117766782A
Cited By
Preparation of nickel phosphide surface epitaxial growth amorphous nickel-cobalt-iron layered double hydroxide electrode and seawater electrolysis application
CN121428597A